(untitled) (Research, Society and Development, 2022)
The production of food for the Brazilian domestic market is mainly produced by Family Farming. The last Agricultural Census, carried out by the Brazilian Institute of Geography and Statistics (IBGE) in 2017, showed that it is responsible for more than 75% of agricultural establishments and employs more than 10 million people, occupying only 23% of the total area of ​​properties. in Brazil, which represents about 80.9 million hectares. This chapter seeks to analyze the main definitions of family farming in Brazil, highlighting the main public policies for these rural subjects between the 1990s and 2000s. Over the decades, family farming has conquered its space in academic discussions, within the scope of institutional and in society, showing above all its multifunctional importance. The main achievements took place in the 1990s, with the creation of the National Program for the Strengthening of Family Agriculture (PRONAF), in 1996, the approval of law No. several other public policies to encourage this agricultural practice that allowed access to lines of credit, technical assistance and a food purchase program.